2006
DOI: 10.1160/th06-07-0367
|View full text |Cite
|
Sign up to set email alerts
|

Platelet microparticle formation and thrombin generation under high shear are effectively suppressed by a monoclonal antibody against GPIbα

Abstract: SummaryWe studied the inhibition of platelet microparticle (MP) formation and thrombin generation under high shear forces. We hypothesized that an inhibitor of the GPIbα-von Willebrand factor (vWF) interaction would be more effective in suppressing MP formation and thrombin generation than GPIIb/IIIa inhibitors. Platelet-rich plasma (PRP) anticoagulated with PPACK (D-Phe-Pro-Arg chloromethyl ketone) was exposed in a coneand-plate viscometer (shear: 5,000 s−1 for5 min) in the presence of antagonists to GPIbα (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
(37 reference statements)
1
26
0
Order By: Relevance
“…Although the major physiological function of CD42b is the adhesion of circulating platelets to vWF in the subendothelial matrix at high shear, which leads to activation of integrin a IIb b III (GPIIb/IIIa) and subsequent aggregation [26], it has also been shown to mediate platelet adhesion under low shear conditions, i.e., in venules [27,28]. Inhibition of CD42b has further been correlated to significantly reduced platelet microparticle formation [29]. At a shear rate of 7.0 AE 3.7 s À1 in hamster venules, CD42b may therefore constitute an important receptor during the hemodynamic response, inasmuch as both platelet aggregation and coagulation prevail.…”
Section: Partial Inhibition Of Cd42b Reduces the Extent Of Laser-indumentioning
confidence: 99%
“…Although the major physiological function of CD42b is the adhesion of circulating platelets to vWF in the subendothelial matrix at high shear, which leads to activation of integrin a IIb b III (GPIIb/IIIa) and subsequent aggregation [26], it has also been shown to mediate platelet adhesion under low shear conditions, i.e., in venules [27,28]. Inhibition of CD42b has further been correlated to significantly reduced platelet microparticle formation [29]. At a shear rate of 7.0 AE 3.7 s À1 in hamster venules, CD42b may therefore constitute an important receptor during the hemodynamic response, inasmuch as both platelet aggregation and coagulation prevail.…”
Section: Partial Inhibition Of Cd42b Reduces the Extent Of Laser-indumentioning
confidence: 99%
“…The effect was more pronounced at shear stress higher than 10 dynes/cm 2 , which confirmed the existence of threshold for SIPA [67,108]. Platelet activation, aggregation and microparticle release, either alone or with RBC, on exposure to normal or pathological shear stress have since been extensively investigated in cone and plate or Couette viscometers [46,51,52,[109][110][111][112]. However, these studies did not consider diverse flow dynamics and their effects on SIPA such as stagnation, flow reversal, local turbulence and eddy currents, as might be expected in vivo when platelets pass through complex geometries.…”
Section: Plateletsmentioning
confidence: 74%
“…This receptor and its interaction with vWF is of particular interest, because it is functional at the high shear rates found in arterial stenosis. Its inhibition results in reduced generation of platelet derived microparticles, thrombin generation and procoagulant activity at high shear forces [17,18]. Furthermore, in vitro studies have shown that platelet membrane glycoprotein polymorphisms (including the Kozak sequence) influence experimental thrombus formation at typical shear rates [30].…”
Section: Discussionmentioning
confidence: 99%
“…The GPIba (5T/C) SNP was of particular interest, since the A1 binding site of von Willebrand factor (vWF) may be activated to bind platelet GPIba under high shear stress, as it occurs in stenotic atherosclerotic lesions [16][17][18][19]. So far, clinical studies investigating the implications of the GPIba (5T/C) polymorphism have yielded controversial results [4][5][6][7]20].…”
Section: Introductionmentioning
confidence: 99%